The use of Toy Story 4 on recount speaking improvement - El Afif, Ahmed Falih; Farida, Alief Noor (ELT Forum: Journal of English Language Teaching, 2025)
This paper investigates the impact of the animated film Toy Story 4 in EFL (English as a Foreign Language) education with emphasis on enhancing speaking recounting ability. With the significance of digital media in education today, films such as Toy Story 4 provide a valuable opportunity for immersive language learning. Using a proposed teaching model, teachers can transform students' watching of the film into their use of language with a recount narrative genre focus. Using the film's interesting plot, characterizations and emotional depth, the model is intended to help students construct cohesive spoken recount. By working with content, which interests students, motivation to learn and engagement is likely increased. The findings indicate that animated films serve as authentic language models, improve comprehension, and advance communicative ability. The proposed educational model contributes to theoretical understanding of multimedia learning and provides a practical approach for teachers wanting to enhance their pedagogical practices as educators of EFL.